WAYS TO INCREASE COMPETITIVENESS AND MANAGEMENT OF SMALL AND MEDIUM BUSINESSES IN CONDITIONS OF DIGITALIZATION OF THE ECONOMY - Tursunov , Imomnazar; Ibodova Дилноза (THE INNOVATION ECONOMY, 2023)
the article describes the role, essence and significance of the digital and innovative economy in increasing the competitiveness of private entrepreneurship, small and medium-sized businesses. Also, proposals were put forward for their development in connection with the integration of science and higher education and internal and external factors of technological development.